Computational design and fabrication of core–shell magnetic molecularly imprinted polymer for dispersive micro‐solid‐phase extraction coupled with high‐performance liquid chromatography for the determination of rhodamine 6G. Issue 12 (27th May 2016) - Xie, Jin; Xie, Jie; Deng, Jian; Fang, Xiangfang; Zhao, Haiqing; Qian, Duo; Wang, Hongjuan
Abstract : A novel core–shell magnetic nano‐adsorbent with surface molecularly imprinted polymer coating was fabricated and then applied to dispersive micro‐solid‐phase extraction followed by determination of rhodamine 6G using high‐performance liquid chromatography. The molecularly imprinted polymer coating was prepared by copolymerization of dopamine and m ‐aminophenylboronic acid (functional monomers), in the presence of rhodamine 6G (template). The selection of the suitable functional monomers was based on the interaction between different monomers and the template using the density functional theory. The ratios of the monomers to template were further optimized by an OA9 (3 4 ) orthogonal array design. The binding performances of the adsorbent were evaluated by static, kinetic, and selective adsorption experiments. The results reveal that the adsorbent possesses remarkable affinity and binding specificity for rhodamine 6G because of the enhanced Lewis acid‐base interaction between the B(Ш) embedded in the imprinted cavities and the template. The nano‐adsorbent was successfully applied to dispersive micro‐solid‐phase extraction coupled to high‐performance liquid chromatography for the trace determination of rhodamine 6G in samples with a detection limit of 2.7 nmol/L. Spiked recoveries ranged from 93.0–99.1, 89.5–92.7, and 86.9–105% in river water, matrimony vine and paprika samples, respectively, with relative standard deviations of less than 4.3%.